2019
DOI: 10.1016/j.renene.2019.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Sunny windy sundays

Abstract: Rapid expansion of wind and solar capacity in Great Britain presents challenges for managing electricity systems. One concern is the reduction in system inertia during periods where renewables provide a high proportion of demand which has led to some networks imposing system nonsynchronous penetration limits. However, given the lack of operational data, the relationship between renewable generation and demand for the full range of meteorological conditions experienced in Great Britain is poorly understood. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Over subhourly to hourly time scales, wind variability is a concern for voltage and frequency regulation 18 and the capacity for the grid to manage rapid changes in supply 19 particularly in conditions where renewable energy production is high and demand is low, due to the low system inertia provided by wind turbines and solar photovoltaic cells 20 . This may lead to increased curtailment of wind farm output in future as the proportion of variable renewable energy sources in the grid increases 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Over subhourly to hourly time scales, wind variability is a concern for voltage and frequency regulation 18 and the capacity for the grid to manage rapid changes in supply 19 particularly in conditions where renewable energy production is high and demand is low, due to the low system inertia provided by wind turbines and solar photovoltaic cells 20 . This may lead to increased curtailment of wind farm output in future as the proportion of variable renewable energy sources in the grid increases 21 .…”
Section: Introductionmentioning
confidence: 99%
“…25 In other countries such as the UK the curtailment percentage is expected to reach almost 4.8%. 26 In Italy and Spain, as well as in many other countries, the curtailment share is laying low, around or even below 2%. However, in a number of western countries where electricity grids are already mature, it is observed that the more the renewables share increase in the energy mix, the higher the curtailment level is.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the periods of low load and high wind availability are the most problematic scenarios [32,33]. However, the Sardinia island is managed covering the load with traditional synchronous generators, while all the wind produced power is exported to the continent through the two HVDCs, which represent the highest contribution in the regulating energy of the island.…”
Section: Simulations and Resultsmentioning
confidence: 99%